Epigenetic Regulation of Fatty Acid Amide Hydrolase in Alzheimer Disease - D'Addario, Claudio; Di Francesco, Andrea; Arosio, Beatrice; Gussago, Cristina; Dell'Osso, Bernardo; Bari, Monica; Galimberti, Daniela; Scarpini, Elio; Altamura, A. Carlo; Mari, Daniela; Maccarrone, Mauro (PloS one, 2012)
Alzheimer disease (AD) is a progressive, degenerative and irreversible neurological disorder with few therapies available. In search for new potential targets, increasing evidence suggests a role for the endocannabinoid system (ECS) in the regulation of neurodegenerative processes. We have studied the gene expression status and the epigenetic regulation of ECS components in peripheral blood mononuclear cells (PBMCs) of subjects with late-onset AD (LOAD) and age-matched controls (CT). We found an increase in fatty acid amide hydrolase (faah) gene expression in LOAD subjects (2.30 ± 0.48) when compared to CT (1.00 ± 0.14; *p<0.05) and no changes in the mRNA levels of any other gene of ECS elements. Consistently, we also observed in LOAD subjects an increase in FAAH protein levels (CT: 0.75 ± 0.04; LOAD: 1.11 ± 0.15; *p<0.05) and activity (pmol/min per mg protein CT: 103.80 ± 8.73; LOAD: 125.10 ± 4.00; *p<0.05), as well as a reduction in DNA methylation at faah gene promoter (CT: 55.90 ± 4.60%; LOAD: 41.20 ± 4.90%; *p<0.05). Present findings suggest the involvement of FAAH in the pathogenesis of AD, highlighting the importance of epigenetic mechanisms in enzyme regulation; they also point to FAAH as a new potential biomarker for AD in easily accessible peripheral cells.